2015
DOI: 10.1175/jcli-d-15-0007.1
|View full text |Cite
|
Sign up to set email alerts
|

Wintertime Atmospheric Response to North Atlantic Ocean Circulation Variability in a Climate Model

Abstract: Maximum covariance analysis of a preindustrial control simulation of the NCAR Community Climate System Model, version 4 (CCSM4), shows that a barotropic signal in winter broadly resembling a negative phase of the North Atlantic Oscillation (NAO) follows an intensification of the Atlantic meridional overturning circulation (AMOC) by about 7 yr. The delay is due to the cyclonic propagation along the North Atlantic Current (NAC) and the subpolar gyre of a SST warming linked to a northward shift and intensificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
3
8
0
Order By: Relevance
“…In particular, the forced atmosphere model experiment supports the existence of a positive atmosphere-ocean feedback. Atmospheric sensitivity to AMOC-related dipolar SST changes in the North Atlantic also has been recently reported from another climate model (Frankignoul et al 2015). The limited observational data also support such an atmospheric sensitivity to mid-latitudinal SST anomalies (Bryden et al 2014;Czaja and Frankignoul 1999;Czaja and Frankignoul 2002).…”
Section: Forced Atmosphere Model Experimentssupporting
confidence: 72%
“…In particular, the forced atmosphere model experiment supports the existence of a positive atmosphere-ocean feedback. Atmospheric sensitivity to AMOC-related dipolar SST changes in the North Atlantic also has been recently reported from another climate model (Frankignoul et al 2015). The limited observational data also support such an atmospheric sensitivity to mid-latitudinal SST anomalies (Bryden et al 2014;Czaja and Frankignoul 1999;Czaja and Frankignoul 2002).…”
Section: Forced Atmosphere Model Experimentssupporting
confidence: 72%
“…During event 2 the changes in ocean circulation and wind increase the transport of sea ice from the Cana- dian Shelf and Baffin Bay to the area of deep convection in the NWA. Other studies revealed that a SST anomaly pattern similar to our study can force a positive NAO phase (e.g., Czaja and Frankignoul, 2002;Frankignoul and Gastineau, 2015;Gastineau and Frankignoul, 2014). This would produce a positive feedback where the positive NAO triggers such a SST anomaly pattern and vice versa, leading the cold climate state to maintain for decades.…”
Section: Sst Anomaly Pattern and Changes In Ocean Circulationsupporting
confidence: 74%
“…3e,f ). These results offer potential predictability of European extreme precipitation on a seasonal scale and in general mark a significant step forward, given the large climate variability and a limited amplitude of the atmospheric response over the Atlantic-European sector 44 , 45 . Although investigation of the underlying physical mechanisms responsible for such a long memory of atmospheric anomalies is beyond the scope of this study, it is anticipated that the following two consecutive processes are in play: the persistence of the atmospheric winter ENSO signal in the stratosphere (after upward propagation of Rossby waves from the troposphere to the stratosphere) considering its slow evolution, and the atmosphere–ocean mixed layer interaction in the North Atlantic 43 , 46 .…”
Section: Resultsmentioning
confidence: 84%